Proton magnetic resonance spectroscopy in Parkinson's disease and progressive supranuclear palsy. Issue 3 (March 1997) - Federico, F; Simone, I L; Lucivero, V; De Mari, M; Giannini, P; Iliceto, G; Mezzapesa, D M; Lamberti, P
Abstract : OBJECTIVES: Proton magnetic resonance spectroscopy (1H-MRS) localised to the lentiform nucleus, was carried out in eight patients with idiopathic Parkinson's disease and five patients with progressive supranuclear palsy. The aim of the study was to assess the concentration of N-acetyl-aspartate (NAA), creatine and phosphocreatine (Cr), and choline containing compounds (Cho) in the putamen and globus pallidus of these patients. METHODS: Peak ratios obtained from patients were compared with those from nine healthy age matched controls. RESULTS: NAA/Cho and NAA/Cr ratios were reduced significantly in patients with progressive supranuclear palsy. CONCLUSION: These results suggest an NAA deficit, due to neuronal loss, in the lentiform nucleus of these patients. 1H-MRS is a non-invasive technique that can provide useful information concerning striatal neuronal loss in the basal ganglia of patients with parkinsonian syndromes.